Peran Kewirausahaan Berbasis Digital Dalam Mengurangi Tingkat Pengangguran - Yusnita Ulfah Munthe; Zuhrinal M. Nawawi (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The creation of entrepreneurs (entrepreneurs) is an alternative solution to various problems in society such as poverty and social inequality, increasing unemployment of productive age and depleting energy supplies, all of which require creative and innovative actions. Entrepreneurship is people who are able to turn an opportunity into a profitable business, which is processed through creativity, innovation and uniqueness in making a product and dares to take all possible risks that come with it and does not make it easy to despair if it fails in building the business. In this case, the author examines that entrepreneurship participates in the development of the country, digital-based entrepreneurship utilizes increasingly sophisticated technology, digital-based entrepreneurship as a solution in reducing the unemployment rate, the number of unemployed in Indonesia, entrepreneurship is something that must be instilled by young people and the people of Indonesia. Keywords: Entrepreneurship, Digital, Unemployment.